PENGARUH KEPUTUSAN PENDANAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA SEKTOR MANUFAKTUR DI INDONESIA - Himawan, Mey Rianaputri (Business Accounting Review, 2016)
The affect of funding decision and dividend policy on firm value had been studied before. However, there was a mix finding of those researches. The aim of this research was to examine the affect funding decision and dividend policy on firm value in manufacturing sector in Indonesia using firm size and profitability.The data in this study were processed using SPSS version 20. The samples used in this study were 475 observations in the manufacturing sector that were listed in Indonesian Stock Exchange in the period of 2010-2014. This study use purposive sampling method. The analysis of the data used in this study was the classical assumption and the hypotheses tested by using multiple regression analysis.The results of this study indicated that funding decisions, firm size and profitabilityÂ  had positive significant affect on firm value while dividend policy did not have influence on firm value